2014
DOI: 10.1371/journal.pone.0107534
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ion Torrent Sequencing to the Assessment of the Effect of Alkali Ballast Water Treatment on Microbial Community Diversity

Abstract: The impact of NaOH as a ballast water treatment (BWT) on microbial community diversity was assessed using the 16S rRNA gene based Ion Torrent sequencing with its new 400 base chemistry. Ballast water samples from a Great Lakes ship were collected from the intake and discharge of both control and NaOH (pH 12) treated tanks and were analyzed in duplicates. One set of duplicates was treated with the membrane-impermeable DNA cross-linking reagent propidium mono-azide (PMA) prior to PCR amplification to differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…After PMA treatment, DNA is extracted, and amplification is typically performed by PCR. PCR-based procedures found to be compatible with PMA treatment include qPCR [ 66 , 67 ], microarrays [ 20 , 68 ], denaturing gradient gel electrophoresis (DGGE) [ 69 ], and amplicon sequencing [ 70 72 ]. In addition to PCR, successful PMA treatment has been reported in combination with loop-mediated isothermal amplification (LAMP) [ 73 ], multiple displacement amplification (MDA) [ 74 ], and metagenomic library construction for low-biomass clean room samples [ 39 ].…”
Section: Common Techniques For Viability Assessmentsmentioning
confidence: 99%
“…After PMA treatment, DNA is extracted, and amplification is typically performed by PCR. PCR-based procedures found to be compatible with PMA treatment include qPCR [ 66 , 67 ], microarrays [ 20 , 68 ], denaturing gradient gel electrophoresis (DGGE) [ 69 ], and amplicon sequencing [ 70 72 ]. In addition to PCR, successful PMA treatment has been reported in combination with loop-mediated isothermal amplification (LAMP) [ 73 ], multiple displacement amplification (MDA) [ 74 ], and metagenomic library construction for low-biomass clean room samples [ 39 ].…”
Section: Common Techniques For Viability Assessmentsmentioning
confidence: 99%
“…As these treatments are already proposed and are due to become mandated in 2017 for newly built vessels travelling outside of any single nation's exclusive economic zone (IMO, ), one question that remains is how effective these treatment approaches will be. This is already an active area of research (e.g., Fujimoto et al., ), and one where next‐generation sequencing approaches, such as those used here, will play a major role. For vessels like the M/V Arctic that exclusively travel within the coastal waters of a single nation, and which will be exempt from new ballast water treatment requirements, the risk of transporting microbes via ballast water will likely remain high.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of microbial communities in ballast water were limited by difficulty in identifying species (but see Tomaru et al., ). The advent of high‐throughput sequencing and metagenomic approaches has begun to fill this knowledge gap and inform our understanding of bacterial communities world‐wide, including in ballast water (e.g., Aridgides et al., ; Brinkmeyer, ; Fujimoto et al., ; Pagenkopp Lohan, Fleischer, Carney, Holzer, & Ruiz, ). These approaches, which typically involve DNA sequencing of the bacterial 16S ribosomal RNA gene (16S rRNA) and subsequent matching of DNA sequences to known bacterial groups, provide a vastly more detailed view of the microbial community in ballast water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Table 5 , there were seven similar instances. It was assumed that no cfu were present when no colonies were recovered; however, the ability to kill bacteria that are capable of entering a viable, but nonculturable state was not determined [13] . In a previous study, Starliper and Watten [7] showed that sodium hydroxide apparently destroyed bacterial cell walls because microscopically, intact cells were not detected after treatments that were the same as administered in the present study.…”
Section: Discussionmentioning
confidence: 99%